2014
DOI: 10.1002/lary.24826
|View full text |Cite
|
Sign up to set email alerts
|

Interim FDGPET/CT for predicting the outcome in patients with head and neck cancer

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Thanks to its ease of use, it was historically the first parameter analyzed. SUVmax was correlated with overall-or disease free survival in 11 studies (Allal et al, 2002;Brun et al, 2002;Castaldi et al, 2012;Chen et al, 2014;Farrag et al, 2010;Higgins et al, 2012;Kitagawa et al, 2003;Machtay et al, 2009;Matoba et al, 2015;Rasmussen et al, 2015;Sanghera et al, 2005). SUVmax allows to identify patients with a high risk of events (death or recurrence).…”
Section: Suvmax and Metabolic Tumor Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its ease of use, it was historically the first parameter analyzed. SUVmax was correlated with overall-or disease free survival in 11 studies (Allal et al, 2002;Brun et al, 2002;Castaldi et al, 2012;Chen et al, 2014;Farrag et al, 2010;Higgins et al, 2012;Kitagawa et al, 2003;Machtay et al, 2009;Matoba et al, 2015;Rasmussen et al, 2015;Sanghera et al, 2005). SUVmax allows to identify patients with a high risk of events (death or recurrence).…”
Section: Suvmax and Metabolic Tumor Volumementioning
confidence: 99%
“…Seven studies (374 patients) evaluated the predictive value of PET performed during RT ± CT (Brun et al, 2002;Castaldi et al, 2012;Chen et al, 2014;Farrag et al, 2010;Hentschel et al, 2011;Min et al, 2016Min et al, , 2015. All but one of them found a correlation between PET parameters RT ± CT and clinical outcome.…”
Section: Predictive Value Of Quantitative Pet Parameters During Chemomentioning
confidence: 99%
“…P ET/CT is critical to the management of patients with head and neck squamous cell carcinoma (HNSCC), given its high accuracy in pretreatment staging and the detection of persistent and recurrent disease after therapy compared with CT or MR imaging, allowing salvage treatment to be initiated in a timely manner. [1][2][3][4][5][6][7][8][9][10][11][12] The high negative predictive value (NPV) of posttreatment PET/CT in patients with a complete response has been established. 10 It was demonstrated in a prospective, randomized controlled trial that concluded that planned neck dissection can be deferred in patients with HNSCC with a complete response on initial posttreatment PET/CT following definitive chemoradiation therapy.…”
mentioning
confidence: 99%
“…One of these studies used metabolic rate derived from plasma FDG level of PET however routine calculation of metabolic rate in clinical practice is not practical for most centres. All, but two studies, included nasopharyngeal cancer and the primary treatment modalities in four studies were heterogeneous, using RT or CRT. Two studies did not confirm the predictive value of mid‐treatment FDG‐PET scans …”
Section: Resultsmentioning
confidence: 99%
“…However, our group reported the absolute values rather than the percentage reduction in metabolic parameters were more predictive of LRFS and DFS but not OS, while TLG was found to be a better predictor than SUV max or MTV. 66 Of seven studies in this group, [67][68][69][70][71][72] only one study 66 reviewed MTV and TLG as predictive indicators of therapeutic response. One of these studies used metabolic rate derived from plasma FDG level of PET 70 however routine calculation of metabolic rate in clinical practice is not practical for most centres.…”
Section: Choice Of Primary Treatmentmentioning
confidence: 99%